2014
DOI: 10.1080/08927014.2014.967232
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide genetic differentiation in the common fouling barnacle,Amphibalanus amphitrite

Abstract: Amphibalanus amphitrite is a common fouling barnacle distributed globally in tropical and subtropical waters. In the present study, the genetic (mitochondrial cytochrome oxidase subunit I) and morphological differentiation in A. amphitrite from 25 localities around the world were investigated. The results revealed three clades within A. amphitrite with a genetic divergence of ~ 4% among clades, whereas there were no diagnostic morphological differences among clades. Clade 1 is widely distributed in both temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 48 publications
2
35
0
1
Order By: Relevance
“…Hence, we attempt to generate a checklist to understand the species diversification and how they distribute on intertidal rocky shores and sandy shores along the coast of Thailand. At least ten different forms of acorn barnacles were diagnosed so far that are classified into 6 genera and 3 families (Chthamalidae, Tetraclitidae and Balanidae), which can be distinguished based on their external shell morphology, including pattern of parietes, opercular plates, and arthropodal characters as described in previous literatures (Ross and Perreault 1999;Chan 2001;Chan et al 2007a, b;Chan et al 2009;Lozano-Cortés and Londoño-Cruz 2013;Chen et al 2014;Hayashi and Chan 2015;Chan and Cheang 2016). Our study also shows that the numbers of species found in the Andaman Sea (8 species) are more than those found in the Gulf of Thailand (6 species).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, we attempt to generate a checklist to understand the species diversification and how they distribute on intertidal rocky shores and sandy shores along the coast of Thailand. At least ten different forms of acorn barnacles were diagnosed so far that are classified into 6 genera and 3 families (Chthamalidae, Tetraclitidae and Balanidae), which can be distinguished based on their external shell morphology, including pattern of parietes, opercular plates, and arthropodal characters as described in previous literatures (Ross and Perreault 1999;Chan 2001;Chan et al 2007a, b;Chan et al 2009;Lozano-Cortés and Londoño-Cruz 2013;Chen et al 2014;Hayashi and Chan 2015;Chan and Cheang 2016). Our study also shows that the numbers of species found in the Andaman Sea (8 species) are more than those found in the Gulf of Thailand (6 species).…”
Section: Discussionmentioning
confidence: 99%
“…Shells exposed and eroded by heavy wave action showed no purple stripes on the external surface. The molecular analysis has confirmed its genetic differentiation which might be due to local adaptation and geographical isolation (Chen et al 2014). Due to hypothesis on human-mediated activities as the main cause of A. amphitrite's distribution across the globe, this species is considered as non-native or introduced species in these examined regions: Hawaii, California, North Carolina, and the Atlantic coast (Carlton et al 2011), whereas it is considered as native in tropical waters (e.g.…”
Section: Amphibalanus Amphitrite (Darwin 1854)mentioning
confidence: 99%
See 3 more Smart Citations